La lúdica como estrategia didáctica en la lectoescritura de los niños de segundo año de básica de la Unidad Educativa San José " La salle". - Chicaiza Pilatasig, Martha Amparito (2021)
This project responds to the problems of children, regarding the development of literacy in the educational process, through playful strategies. The resolution of the project had as objective; design and apply a didactic guide for playful activities for the literacy process in children of second grade of the San José "La Salle" school. The methodology used in this research has required a quantitative approach. For this reason, novelty and originality were a fundamental part in the achievement of the project, since play had an extraordinary amount of forms, means, and satisfactions, among which the game was one of them. In addition, we can express ourselves in many ways such as singing, reading, dancing, enjoying a good movie, practicing a sport or just dreaming. Also, we used the deductive method based on existing theories, which gave the research a theoretical utility, because there are historical foundations of an educational nature in relation to playing. However, the results obtained when carrying out the proposal were very satisfactory, so that the didactic guide of recreational activities addressed a topic of great importance for the educational institution. At the same time, it contributed to the improvement in the quality of education by contributing to the renewal and professional updating of the teachers, the activities of the guide such as hopscotch of syllables, putting together words with balloons, word lottery among others; significantly improved children's literacy learning